Birds of a feather (might not) flock together: Exploring the complex interplay of motivation, autonomy and positive emotions in predicting anxiety levels in Hungarian secondary school language learners - Albert, Ágnes; Csizér, Kata (Studies in Second Language Learning and Teaching, 2025)
Due to its importance in second/foreign language (L2) learning, anxiety appears to be one of the most important individual differences (IDs). Still, learners’ experiences of anxiety tend to vary considerably, so we set out to investigate the anxiety levels, reported in our large-scale quantitative study involving 1,152 secondary school language learners in Hungary, by different learner groups. Cluster analysis was employed to create learner groups with different profiles, which were based on the learners’ motivation, autonomy and selected positive emotions, that is, hope, pride, enjoyment and curiosity, thereby forming three profiles for autonomy and four groups for motivation and positive emotions. The resulting groupings were then entered into a univariate general linear model (GLM) to predict the anxiety levels of the learners. The results of the three-way analysis of variance (ANOVA) showed significant main effects for motivation, autonomy and positive emotions, two significant second-order interactions between motivation and autonomy and motivation and positive emotions, and a significant third-order interaction between motivation, autonomy and learners’ positive emotions. It appears that learners’ motivation, autonomy, and positive emotion profiles jointly determined the level of anxiety experienced by them. The most important implication of our results is that simple linear relationships are untenable when it comes to describing the interplay of these individual differences both concerning the theoretical advancement of our knowledge as well as the pedagogical knowledge of English teachers.